Maibaum - Adelmann, Irene; Kapfhammer, Günther; Ach, Manfred; Friedel, Helmut (München : Kulturreferat der Landeshauptstadt München, 1987)
Banana, Charly ; Brodwolf, Jürgen ; Buisman, Sjoerd ; Christiansen, Henning ; Dossi, Ugo ; Fischer, Lili ; Gappmayr, Heinz ; Gerhart, Nikolaus ; Gerz, Jochen ; Guiraud, Nicole ; Gosewitz, Ludwig ; Helms, Dietrich ; Julius ; Katase, Kazuo ; Klepsch, Axel ; Kutscher, Vollrad ; Meyer-Rogge, Jan ; Mields, Rune ; Nagasawa, Hidetoshi, Nele, E.R. ; Oppermann, Anna ; Pallanca, Heike ; Rosenbach, Ulrike ; Rosenstock, Fried ; Saito, Takako ; Schäuffelen, Konrad Balder ; Scharz, Martin ; Schwegler, Fritz ; Stenvert, Curt ; Nils-Udo ; Ulrichs, Timm ; von Windheim, Dorothea
Maibaum, Ausstellung München, 1987
boek